2013
DOI: 10.1136/bmjopen-2013-003963
|View full text |Cite
|
Sign up to set email alerts
|

Profile, cost and pattern of prescriptions for polymedicated patients in Catalonia, Spain

Abstract: ObjectivesPolypharmacy is one of the main management issues in public health policies because of its financial impact and the increasing number of people involved. The polymedicated population according to their demographic and therapeutic profile and the cost for the public healthcare system were characterised.DesignCross-sectional study.SettingPrimary healthcare in Barcelona Health Region, Catalonia, Spain (5 105 551 inhabitants registered).ParticipantsAll insured polymedicated patients. Polymedicated patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…In our study, participants treated with antidepressant medication were at greater risk for polypharmacy (OR 9.07; 95% CI 8.94 to 11.02); similar conclusions have also been found by other studies . It would appear that particularly in women, antidepressants, hypnotics, sedatives and anxiolytics may be typical indicators for polypharmacy .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, participants treated with antidepressant medication were at greater risk for polypharmacy (OR 9.07; 95% CI 8.94 to 11.02); similar conclusions have also been found by other studies . It would appear that particularly in women, antidepressants, hypnotics, sedatives and anxiolytics may be typical indicators for polypharmacy .…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that an increase in age correlates positively with the total number of medicines being taken, hence the occurrence of polypharmacy. Evidence showing that women of advanced age tend to be on a polypharmacy regime is solid . Conversely, few studies have reported a correlation between polypharmacy and being male .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 17 A polymedicated user in the present study was defined as someone receiving 16 or more drugs in a month, according to the Efficiency Indicators in Primary Care, which are periodically evaluated by an internal Management Committee in the Catalan Health Service (macromanagement level). 18 …”
Section: Methodsmentioning
confidence: 99%